Antioxidant and Neuroprotective Effects of the First Tryptophyllin Found in Snake Venom (Bothrops moojeni) - Dematei, Anderson; Costa, Samuel Ribeiro; Moreira, Daniel C.; Barbosa, Eder Alves; Friaça Albuquerque, Lucas F.; Vasconcelos, Andreanne G.; Nascimento, Tiago; Silva, Pedro Costa; Silva-Carvalho, Amandda É.; Saldanha-Araújo, Felipe; Silva Mancini, Mariana Camargo; Saboia Ponte, Luis Gustavo; et al. (American Chemical Society (ACS), 2022)
In this study, we report the isolation, characterization, and synthesis of the peptide BmT-2 belonging to the tryptophyllins family, isolated from the venom of the snake Bothrops moojeni. This is the first time a tryptophyllin is identified in snake venom. We tested whether BmT-2 had cytotoxic effects and antioxidant activity in a set of experiments that included both in vitro and cell-based assays. BmT-2 presented a radical scavenging activity toward ABTS• and AAPH-derived radicals. BmT-2 protected fluorescein, DNA molecules, and human red blood cells (RBCs) from free radicals generated by the thermal decomposition of AAPH. The novel tryptophyllin was not toxic in cell viability tests, where it (up to 0.4 mg/mL) did not cause hemolysis of human RBCs and did not cause significant loss of cell viability, showing a CC50 > 1.5 mM for cytotoxic effects against SK-N-BE(2) neuroblastoma cells. BmT-2 prevented the arsenite-induced upregulation of Nrf2 in Neuro-2a neuroblasts and the phorbol myristate acetate-induced overgeneration of reactive oxygen species and reactive nitrogen species in SK-N-BE(2) neuroblastoma cells. Electronic structure calculations and full atomistic reactive molecular dynamics simulations revealed the relevant contribution of aromatic residues in BmT-2 to its antioxidant properties. Our study presents a novel peptide classified into the family of the tryptophyllins, which has been reported exclusively in amphibians. Despite the promising results on its antioxidant activity and low cytotoxicity, the mechanisms of action of BmT-2 still need to be further elucidated.